2008
DOI: 10.1200/jco.2007.15.7545
|View full text |Cite
|
Sign up to set email alerts
|

Irinotecan Plus Carboplatin Versus Oral Etoposide Plus Carboplatin in Extensive Small-Cell Lung Cancer: A Randomized Phase III Trial

Abstract: IC prolongs survival in ED SCLC with slightly better scores for QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
168
0
13

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 153 publications
(181 citation statements)
references
References 19 publications
0
168
0
13
Order By: Relevance
“…SCLC patients (both ED and LD) who had responded to treatment (67, Bottomley et al, 2008;Slotman et al, 2009) reported higher scores than patients who had not been treated. Systemic treatment naïve ED SCLC patients had the lowest scores overall (44.7, Hermes et al, 2008). As expected, all SCLC EORTC QLQ-C30 scores were lower the normative global health status/QoL scores provided by the EORTC of 71.2 (Scott et al, 2008).…”
Section: Global Hrqolmentioning
confidence: 63%
See 4 more Smart Citations
“…SCLC patients (both ED and LD) who had responded to treatment (67, Bottomley et al, 2008;Slotman et al, 2009) reported higher scores than patients who had not been treated. Systemic treatment naïve ED SCLC patients had the lowest scores overall (44.7, Hermes et al, 2008). As expected, all SCLC EORTC QLQ-C30 scores were lower the normative global health status/QoL scores provided by the EORTC of 71.2 (Scott et al, 2008).…”
Section: Global Hrqolmentioning
confidence: 63%
“…The 27 publications included in this review reported results from interventional clinical trials assessing HRQoL as an endpoint (n = 18); 11 were randomized but not controlled (Thatcher et al, 2005;Eckardt et al, 2006;Reck et al, 2006Reck et al, , 2012Hermes et al, 2008;Lee et al, 2009;Le Pechoux et al, 2011;Nagel et al, 2011;Wolfson et al, 2011;Satouchi et al, 2014;Sekine et al, 2014) (see Table 2), four were randomized controlled trials (RCTs) (Giaccone et al, 2005;O'Brien et al, 2006;Bottomley et al, 2008;Slotman et al, 2009) (see Table 3) and three were nonrandomized interventional studies (Fennell et al, 2007;Araujo et al, 2009;Eckardt et al, 2009) (see Table 4). The remaining publications were real world (n = 7) (Jatoi et al, 2005;Chen et al, 2007Chen et al, , 2008Chen et al, , 2012Rolke et al, 2008;Kohli et al, 2010;Nakahara et al, 2015) (see Table 5) and mixed-methods studies (n = 2) (Westerman et al, 2007(Westerman et al, , 2008) (see Table 6).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations